The influence of DACCIWA radiosonde data on the quality of ECMWF analyses and forecasts over southern West Africa. (3rd March 2020) - van der Linden, Roderick; Knippertz, Peter; Fink, Andreas H.; Ingleby, Bruce; Maranan, Marlon; Benedetti, Angela
Abstract: During the DACCIWA (Dynamics–Aerosol–Chemistry–Cloud Interactions in West Africa) field campaign ∼900 radiosondes were launched from 12 stations in southern West Africa from 15 June to 31 July 2016. Subsequently, data‐denial experiments were conducted using the Integrated Forecasting System of the European Centre for Medium‐range Weather Forecasts (ECMWF) to assess the radiosondes' impact on the quality of analyses and forecasts. As observational reference, satellite‐based estimates of rainfall and outgoing long‐wave radiation (OLR) as well as the radiosonde measurements themselves are used. With regard to the analyses, the additional observations show positive impacts on winds throughout the troposphere and lower stratosphere, while large lower‐tropospheric cold and dry biases are hardly reduced. Nonetheless, downstream, that is farther inland from the radiosonde stations, we find a significant increase (decrease) in low‐level night‐time temperatures (monsoon winds) when incorporating the DACCIWA observations, suggesting a possible linkage via weaker cold air advection from the Gulf of Guinea. The associated lower relative humidity leads to reduced cloud cover in the DACCIWA analysis. Closer to the coast and over Benin and Togo, DACCIWA observations increase low‐level specific humidity and precipitable water, possibly due to changes in advection and vertical mixing. During daytime, differences between the two analyses are generally smaller at low levels. With regard to the forecasts, the impact of the additional observations is lost after a day or less. Moderate improvements occur in low‐level wind and temperature but also in rainfall over the downstream Sahel, while impacts on OLR are ambiguous. The changes in precipitation appear to also affect high‐level cloud cover and the tropical easterly jet. The overall rather small observation impact suggests that model and data assimilation deficits are the main limiting factors for better forecasts in West Africa. The new observations and physical understanding from DACCIWA can hopefully contribute to reducing these issues. Abstract : Data from radiosondes launched in southern West Africa during the DACCIWA field campaign in 2016 were employed in data‐denial experiments using the ECMWF forecast system. The results show that relatively large impacts can be found for night‐time and early morning low‐level winds (top) and temperatures (bottom), particularly downstream (i.e. north) of the radiosonde stations. The positive impact does not extend beyond 1 day in forecasts. Model errors and data assimilation are most probably the main factors limiting better forecasts.